2014
DOI: 10.1177/1460408614530946
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic fractures around total knee arthroplasty

Abstract: Periprosthetic fractures around total knee replacements were first reported more than 30 years ago. They are becoming more common. Various associated risk factors have been described. Treatment options for femoral fractures around total knee replacements include non-operative management, locked plates, retrograde intramedullary nails and revision arthroplasty. Periprosthetic fractures of the tibia and patella are also described, but are less common. This review article provides an overview of the epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The classic predisposing factors are osteopenia, infection and osteolysis, female gender, older age, anterior femoral notching, and revision arthroplasty 3 . However, Singh et al, 1 in a retrospective study of 21,723 arthroplasties, found that the only significant factor for fracture in primary TKA was patient's age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The classic predisposing factors are osteopenia, infection and osteolysis, female gender, older age, anterior femoral notching, and revision arthroplasty 3 . However, Singh et al, 1 in a retrospective study of 21,723 arthroplasties, found that the only significant factor for fracture in primary TKA was patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…The status of the implant fixation should be established; in case of loosening (Rorabeck type III ), TKA revision must be performed 3 . For type I and II fractures, there are two fixation options: retrograde intramedullary nail and locking plates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations